Circular economy to respond environmental challenge: Package water business case - Ratih Prajnaparamita Anggraeni (World Nutrition Journal, 2020)
In Indonesia, although the total recycling rate of plastic below 10%; PET bottle is still categorized as has a high recycling rate (above 50%).4 And since not all plastic are the same, such reference is crucial to define what kind of plastic material can be chosen and what type of product that can use the post-recycling materials.